Determinants of Exclusive Breastfeeding Practices Among Informal Sector Working Mothers - Lu'lu Nafisah; Yuditha Nindya Kartika Rizqi; Leni Maryati (Association of Public Health Scholars based in Faculty of Public Health, Sriwijaya University, 2025)
Exclusive Breastfeeding (EBF) is essential for optimal infant growth, development, and disease protection. Despite its well-documented benefits, global EBF rates remain suboptimal, and the rate in Indonesia (52%) remains below the WHO's 2030 target. This study investigates factors affecting EBF among working mothers in the informal sector in Banyumas Regency, Indonesia, a particularly vulnerable group facing challenges like inadequate maternity leave and limited workplace support. A cross-sectional study was conducted with 350 informal sector working mothers. Data on sociodemographic, maternal, work-related, and social factors were collected using a validated and reliable questionnaire and analyzed using univariate, bivariate (chi-square), and multivariate (logistic regression) methods. The results showed that 68.2% of mothers successfully practiced EBF, a slightly higher rate than reported in previous studies. Multivariate analysis revealed that strong family support (AOR=18.098, 95% CI: 7.396 – 44.285, p<0.001), mother's good knowledge, and positive attitudes were powerful enablers of EBF. Conversely, several counter-intuitive associations were found: lower maternal education (AOR=16.008, 95% CI: 3.422 – 74.894, p<0.001), longer work duration (>8 hours/day; AOR=7.434, 95% CI: 3.364 – 16.426, p<0.001), primiparous status (AOR=3.998, 95% CI: 1.830 – 8.734, p=0.001), non-performance of immediate breastfeeding (AOR=8.535, 95% CI: 3.523 – 20.675, p<0.001), and non-consumption of breast milk boosters (AOR=5.229, 95% CI: 1.284 – 21.291, p=0.021) were all independently associated with a higher likelihood of EBF. Maternal age was not found to be a significant determinant. This study revealed highly complex, context-specific determinants of exclusive breastfeeding (EBF) among informal sector working mothers, often diverging from patterns observed in formally employed populations. Key findings underscore the need for tailored, context-sensitive interventions focusing on strengthening informal social support, advocating for adaptive work accommodations, and providing targeted education.